Analytical Science - Chapter 4 - Woodget, Brian (The University of Hull)
This chapter considers the mathematical procedures used to obtain quantitative analytical measurements. It includes, units of measurement, use of calibration graphs, standard addition and internal standard procedures. It compares the uses of absolute and comparative techniques to obtain analytical data and reviews volumetric and gravimetric procedures.